Oxford Handbooks Online 2010
DOI: 10.1093/oxfordhb/9780199738632.013.0037
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Variation and Change

Abstract: Links to third party websites are provided by Oxford in good faith and for information only. Oxford disclaims any responsibility for the materials contained in any third party website referenced in this work. Contents List of figures viii List of tables xii List of figures 1.1 Research perspectives within the lexeme-lection-lect triangle 1.2 An example of denotationally expanded lexicology 2.1 Semasiological structure of vest 2.2 Graphical representation of the steps in the distributional workflow 3.1 2D repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 90 publications
0
13
0
3
Order By: Relevance
“…those related to the expression of feelings and attitudes-a set of uses that is obviously quite different from the basic 'caused reception' uses of the construction, semantically. In present-day lexicology, a distinction is made between qualitative and quantitative shifts in semantic structure: the latter term refers to fluctuations in the structural weight of the various senses or clusters of uses of a given lexical item (see, e.g., Geeraerts 1997, Grondelaers et al 2007. Analogously, Similarly to the distinction between qualitative and quantitative valency shifts in individual verbs, we can distinguish between qualitative and quantitative semantic shifts at the level of the argument structure construction.…”
Section: Quantitative Shifts In Constructional Semanticsmentioning
confidence: 99%
See 1 more Smart Citation
“…those related to the expression of feelings and attitudes-a set of uses that is obviously quite different from the basic 'caused reception' uses of the construction, semantically. In present-day lexicology, a distinction is made between qualitative and quantitative shifts in semantic structure: the latter term refers to fluctuations in the structural weight of the various senses or clusters of uses of a given lexical item (see, e.g., Geeraerts 1997, Grondelaers et al 2007. Analogously, Similarly to the distinction between qualitative and quantitative valency shifts in individual verbs, we can distinguish between qualitative and quantitative semantic shifts at the level of the argument structure construction.…”
Section: Quantitative Shifts In Constructional Semanticsmentioning
confidence: 99%
“…Quantitative shifts are shifts in the structural weight or relative degree of salience of the various uses of a construction: a particular subsense or cluster of uses which was quite central to the construction's meaning at a given period in time may occupy a more peripheral position in the construction's semantic network at a later time, or vice versa. (see Grondelaers et al 2007 for a brief overview of qualitative versus quantitative aspects of semantic structure). Such diachronic shifts along the coreperiphery axis can be identified through a more quantitative analysis of frequency data.…”
Section: Quantitative Shifts In Constructional Semanticsmentioning
confidence: 99%
“…Discovering the motivations that trigger the change of current meaning(s) of a word from their original usage can reveal interesting aspects about human linguistic and social behaviour. Studies have shown that the change can be in one of the meanings of a word or more or even in the word's loss of meaning LP LX (2) (Grondelaers et al 2007). Every word has a variety of senses which can be changed, added to or lost over time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lectal features of the items involved are not only able to determine the occurrence of synonyms across lectal varieties, but can also be responsible for motivating the differences of prototypical structure between synonyms. The third hypothesis is that synonym competition sheds light upon processes of language variation and change (Grondelaers, Geeraerts & Speelman 2007;Geeraerts & Speelman 2010), including convergence and divergence processes between lectal varieties and the processes of linguistic stratification and standardization (Soares da Silva 2010, 2012, 2014. Focusing on the interplay between conceptual and social aspects of language variation and change, this study subscribes to the framework of Cognitive Sociolinguistics (Kristiansen & Dirven 2008;Geeraerts, Kristiansen & Peirsman 2010), an emerging extension of Cognitive Linguistics (Geeraerts & Cuyckens 2007) as a meaning-oriented and usage-based approach to language.…”
Section: Introductionmentioning
confidence: 99%